Thermodynamic and configurational entropy of quantum Schwarzschild geometries - Casadio, R.; da Rocha, R.; Giusti, A.; Meert, P. [UNESP] (Elsevier, 2024)
We study different entropies for coherent states representing the geometry of spherically symmetric compact systems. We show that the thermodynamic entropy reproduces the Bekenstein-Hawking result in the presence of thermal modes at the Hawking temperature if the object is a black hole and saturates the Bekenstein bound for more general compact objects. We also analyse the information entropy of the quantum coherent state without radiation and find further support against the singular Schwarzschild geometry.